Application of actuarial models to predict future outcomes and manage risks - Comprehensive Study on Actuarial Modeling Using Life Tables AM92 – - ZADOUERKEB , Mounir; ZADOUERKEB , Fouzia (Journal of Excellence for Economics and Management Research)
This study investigates the predictive and risk‐management capabilities of actuarial models through a comprehensive analysis of Life Tables AM92. The research addresses the growing need for accurate forecasting of future liabilities in the insurance and pension sectors, where traditional methods often fall short amid evolving demographic and economic landscapes. Employing a robust quantitative framework, the study integrates empirical data analysis, simulation techniques, and sensitivity testing to refine actuarial estimates. In doing so, it leverages both conventional actuarial practices and modern statistical methodologies to enhance the precision of mortality and survival predictions. Key findings demonstrate that Life Tables AM92 serve as a reliable benchmark for estimating mortality rates, survival probabilities, and the present value of future payouts. The results reveal that incorporating advanced statistical techniques substantially improves model accuracy, thereby providing insurers and policymakers with a more effective tool for financial risk management. These insights underscore the importance of continuous model validation and the adoption of emerging technologies in actuarial practices, paving the way for more sustainable and informed decision-making in the realm of risk management